2012
DOI: 10.1161/circresaha.112.268946
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Control of Cellular Life, Stress, and Death

Abstract: Since the discovery that mitochondrial membrane permeabilization represents a critical step in the regulation of intrinsic apoptosis, mitochondria have been viewed as pluripotent organelles, controlling cell death as well as several aspects of cell survival. Mitochondria constitute the most prominent source of ATP and are implicated in multiple anabolic and catabolic circuitries. In addition, mitochondria coordinate cell-wide stress responses, such as autophagy, and control nonapoptotic cell death routines, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
325
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 452 publications
(335 citation statements)
references
References 127 publications
2
325
1
7
Order By: Relevance
“…7,61 In contrast to uncontrolled tissue damage, programmed cell death is an important mechanism to maintain tissue homeostasis. 15,17,18,62,63 In the context of sepsis, Clark et al 64 found that PLT interaction with neutrophils can mediate endothelial damage in the presence of lipopolysaccharide. Although cell damage was measured by PI uptake, endothelial apoptosis was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…7,61 In contrast to uncontrolled tissue damage, programmed cell death is an important mechanism to maintain tissue homeostasis. 15,17,18,62,63 In the context of sepsis, Clark et al 64 found that PLT interaction with neutrophils can mediate endothelial damage in the presence of lipopolysaccharide. Although cell damage was measured by PI uptake, endothelial apoptosis was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism might ensure that cellular damage can be cleared by autophagy before it induces unwarranted cell death, especially in post-mitotic cells like neurons (93). As described above, the autophagic machinery can also detect and dispose damaged mitochondria that otherwise release pro-apoptotic factors and harmful reactive oxygen species, thereby offering cellular self-rescue (94). This mechanism might contribute to the commonly observed increase of autophagy in skeletal muscle myopathies.…”
Section: Autophagy Induction Suffices To Promote Longevitymentioning
confidence: 94%
“…[239][240][241] The externalization of phosphatidylserine (a phospholipid normally restricted to the inner leaflet of the plasma membrane) indeed accompanies multiple (though not all) instances of apoptotic cell death, 16,[242][243][244][245] while the permanent dissipation of the Dc m as a result of mitochondrial outer membrane permeabilization (MOMP) constitutes one of the major hallmarks of mitochondrial apoptosis. 17,18,246,247 Of note, DiOC 6 (3) is not compatible with fixation, but other Dc m -sensitive probes are, including chloromethyltetramethylrosamine (absorption/emission peaks: 554/576 nm). 248 MOMP is accompanied by the massive activation of caspase-9 and -3, while caspase-8 is required for ICD upstream of MOMP.…”
Section: Cell Deathmentioning
confidence: 99%